# Question #dd308

Jan 17, 2018

$Y = 36$

#### Explanation:

Solve using opposite operations :)

$\frac{Y}{6} - 5 = 1$

$\frac{Y}{6} - 5 \textcolor{red}{+ 5} = 1 \textcolor{red}{+ 5}$

$\frac{Y}{6} = 6$

$\frac{Y}{6} \textcolor{red}{\times 6} = 6 \textcolor{red}{\times 6}$

$Y = 36$

I hope that helps :)

Jan 17, 2018

$y = 36$

#### Explanation:

"Order of Operations" tells us in what order to do things to an equation. Generally, when doing math, the order is PEMDAS.

P $\to$ Parentheses. This means do everything within parentheses. If there are multiple, do them all in the PEMDAS order as well. (Useful to know, but useless in this problem)

E $\to$ Exponent. If you have anything to the power of another thing, figure those out first. (Useful to know, useless for this problem)

MD $\to$ Multiplication & Division. Any sort of multiplication or division in the problem, you do these next. If there's multiple of them, you do them in the order from left to right.

AS $\to$ Addition & Subtraction. Any sort of addition and subtraction in the problem, you do these last. If there's multiple of them, do them from left to right.

$\frac{y}{6} - 5 = 1$

you are solving for the value, rather than just simplifying an expression. So we do this in the opposite order (SADMEP).

First, we see there's subtraction of a 5. So let's undo that by adding 5 to each side.

$\frac{y}{6} \textcolor{red}{\cancel{- 5}} + \textcolor{red}{\cancel{5}} = 1 + 5$
$\frac{y}{6} = 6$

Next, we see there's division. So let's undo that by multiplying each side by 6.

$\frac{y}{\textcolor{red}{\cancel{6}}} \cdot \textcolor{red}{\cancel{6}} = 6 \cdot 6$

Simplify this final step, and we get

$y = 36$